0401 Cognitive Behavioral Therapy for Insomnia is Equally Effective for Insomnia Patients With Short and Longer Objective Sleep Duration. (27th April 2018) - Yang, C; Huang, Y; Jan, Y; Lee, H
Abstract: Introduction: Insomnia with short objective sleep duration has been proposed to be a specific phenotype of insomnia since it was found to be associated with higher risks of cardiometabolic and neuropsychiatric disorders. One recent study further reported that insomnia with actigraphy-defined short sleep duration (<6 h) are less responsive to CBT-I than those with longer sleep duration (≥6 h). The present study examined whether insomnia patients with polysomnography-defined short sleep duration would also have blunted response to CBT-I. Methods: 88 insomnia patients (mean age = 44.36 years, 61 females), without comorbid psychiatric, medical, or sleep disorders, participated in this study. They were divided into a short-sleep-duration group (<6 h; N=22; mean age = 42.54 years) and a longer-sleep-duration group (≥6 h; N=44; mean age = 44.97) based on one night of PSG. They all went through a 6-session CBT-I program over a 7-week period, and were required to complete the Insomnia Severity Index (ISI) before and after treatment, and to keep sleep logs throughout the treatment period. Results: 2 (short-sleep vs longer-sleep group) X 2 (pre-treatment vs post-treatment) two-way ANOVAs were conducted. The results showed significant treatment main effects on the ISI, and on sleep efficiency, wake time after sleep onset, and self-rated sleep quality and daytime functioning from sleep logs, but no significant group main effects and interactions. Both groups gained significant improvements in these variables. No significant effects were found for total sleep time and sleep onset latency. Conclusion: Our results showed that CBT-I is equally effective for insomnia patients with short and near-normal objective sleep duration. These results are inconsistent with the previous finding that insomnia patients with objective short sleep duration had a blunted response to CBT-I. The inconsistency might be due to the different measures used to define objective sleep duration and/or the difference in the components included in the CBT-I programs. Further studies are needed to address these issues. Support (If Any): This study is partially supported by the Ministry of Science and Technology, Taiwan (NSC104-2410-H-004-044-MY3).